Evaluasi Kadar Kurkumin dalam Jamu Tradisional Kunir Asam yang Dijual di Pasar Kota Gede Bulan Februari 2015 - Yusuf, Fitrilya Mustikahati; Nurkhasanah, Nurkhasanah (Pharmaceutical Sciences and Research, 2015)
Javanese women often consume kunir asam to relieve dysmenorrhea symptom. It is a traditional herbal medicine which is conventionally prepared from curcuma domestica. One of the active compound of curcuma domestica is curcumin. The purpose of this research is to determine the amount of curcumin available in kunir asam selling in daily market of Kota Gede. Curcumin level in daily batches consistency was also evaluated. Curcumin analysis was conducted by qualitative and quantitative tests by TLC densitometry method. A total of 50.0 ml kunir asam was extracted with 25.0 ml of chloroform, and then the mixture was dried by evaporation. The dried residue of extract was then reconstituted in 5.0 ml of 96% ethanol. 5 μl of sample supernatant and standard solutions spotted on the plates of silica gel 60 F254 that has been activated previously. The organic solvent mixture comprise of chloroform: ethanol: glacial acetic acid (94:5:1) was used as the mobile phase for elution, and the spots were then analyzed by using densitometry at wavelength of 425 nm. Curcumin levels was calculated by inputting the size of spot area data into the standard curve linear regression equation of curcumin concentration versus the size of spot area. The data analysis was performed by normality test Kolmogorov-Smirnov test, Levene test of homogeneity followed by Post Hoc / Test LSD (Least Significant Difference) or Mann Whitney. TLC analysis conducted on four samples of “kunir asam” displayed a disparities on the curcumin level between the three days of sampling in a row. Statistical analysis of the curcumin content in traditional herbal medicine of “kunir asam” samples showed that the levels were not consistent in the three days of the examination. Curcumin levels in all four samples were also shows a significant difference in variations.